2012
DOI: 10.3727/096368911x623925
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Stem Cell Treatment Prevents Renal Disease Progression

Abstract: Adipose tissue-derived stem cells (ASCs) are an attractive source of stem cells with regenerative properties that are similar to those of bone marrow stem cells. Here, we analyze the role of ASCs in reducing the progression of kidney fibrosis. Progressive renal fibrosis was achieved by unilateral clamping of the renal pedicle in mice for 1 h; after that, the kidney was reperfused immediately. Four hours after the surgery, 2 ´ 10 5 ASCs were intraperitoneally administered, and mice were followed for 24 h posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 64 publications
5
62
0
Order By: Relevance
“…Western blotting was performed as previously described. 22,30 The primary antibodies were obtained from the following sources: anti-phospho-p65 (no. 3039), anti-phospho-Smad3 (no.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed as previously described. 22,30 The primary antibodies were obtained from the following sources: anti-phospho-p65 (no. 3039), anti-phospho-Smad3 (no.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…[13][14][15] In the context of kidney, IL-10 has been reported to effectively suppress the progression of acute and chronic renal damage in vivo. [16][17][18][19][20][21][22] However, the role of IL-10 in renal tubulointerstitial fibrosis has not been studied. Here, we used IL-10 À / À mice [23][24][25][26] with unilateral ureteral obstruction (UUO), a well-established model for kidney fibrosis, to investigate the roles of IL-10 in the progression of renal fibrosis.…”
mentioning
confidence: 99%
“…53,54 Over the long term, the acute inflammatory reaction manifests as a chronic pattern because the chamber acts as a nonremovable injury stimulation.…”
mentioning
confidence: 99%
“…Although most of the topically applied MSCs were observed to be remained on the surface of the recipient kidney in our study, the potential biological roles of these MSC should not be overlooked. It was postulated these MSCs might execute their biologic roles via paracrine and/or endocrine pathways, including mitogenic, antiapopotic, anti-inflammatory and angiogenic effects to support the regeneration of local kidney cells [8,9,26,41,42]. In fact, from our study, we had demonstrated downregulation of the expressions of caspase-3 (indicator of apoptosis) and endothelin-1 (indicator of endothelial damage), and upregulation of the expression of NQO-1 (anti-oxidative marker) in kidneys treated with topical MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Renoprotective effects have been shown in preclinical studies [8][9][10][11][12][13]. It is believed that MSCs ameliorate renal injury by direct differentiation into tubular epithelial cells or by the release of paracrine/ endocrine factors that restore renal structure and function [8,9].…”
Section: Introductionmentioning
confidence: 99%